Validity, reliability, and significance: empirical methods for NLP and data science - Riezler, Stefan; Hagmann, Michael (Springer Nature Switzerland, 2024)
Preface -- Acknowledgments -- Introduction -- Validity -- Reliability -- Significance -- Worked-Through Example: Analyzing Inferential Reproducibility -- Bibliography.